Solvent-Dependent Efficacy of Moringa oleifera Leaf Extracts on Methicillin-Resistant Staphylococcus aureus: Assessments on Antibacterial and Antioxidant Properties - Ilakhiya Paavai Arunasalam; Seri Narti Edayu Sarchio; Nur Liyana Daud; Suhaili Shamsi; Mohd Nasir Mohd Desa; Muhamad Hafiz Abd Rahim (Tropical Life Sciences Research, 2026)
The global surge in antibiotic resistance, particularly methicillin-resistant Staphylococcus aureus (MRSA), presents a significant public health challenge and emphasises the necessity for alternative therapeutic strategies. Moringa oleifera is rich in bioactive phytochemicals with established antimicrobial properties, however, the impact of various extraction solvents on its efficacy against MRSA has not been thoroughly investigated. This study offers a direct comparison of ethanolic, methanolic and aqueous M. oleifera leaf extracts (MOLE) to identify the optimal solvent for enhancing antibacterial and antioxidant activities. MOLE was extracted through maceration, and antibacterial activity against MRSA was assessed using colony-forming unit (CFU) assays at concentrations of 50 mg/mL, 100 mg/mL and 200 mg/mL, with vancomycin serving as the positive control. Antioxidant capacity was quantified using the ferric reducing antioxidant power (FRAP) assay, while phytochemical profiles characterised via liquid chromatography–mass spectrometry (LC–MS). The ethanolic extract exhibited the highest bioactivity, achieving complete MRSA inhibition at 100 mg/mL and demonstrating efficacy statistically comparable to vancomycin at 50 mg/mL. It also showed significantly greater antioxidant capacity across all tested concentrations. LC–MS analysis linked this enhanced activity to a richer composition of flavonoids and phenolic acids in the ethanolic extract. In summary, ethanol emerged as the most effective solvent for extracting antibacterial and antioxidant compounds from M. oleifera leaves. The findings underscore the potential of ethanolic MOLE as a natural therapeutic candidate against MRSA, warranting further investigation in preclinical models.